Developing and implementing a public health and criminological approach to tackling sexual abuse: prevention, treatment and integration - McCartan, Kieran; Eason, Anne; Senker, Sarah; Addis, Nick; Porter, Cody (Palgrave studies in risk, crime and society, 2025)
This edited collection draws together and contextualises research on the Epidemiological Criminology (EpiCrim) approaches to sexual abuse carried out by the University of West England (UWE), Bristol. EpiCrim sees crime and offending behaviour, including sexual abuse, as a public health issue and advocates that to prevent first time or repeat offending behaviour we have to work in a bespoke way across a number of populations (individual, interpersonal, community, and societal). The book introduces the area of EpiCrim and how it works to address sexual abuse, before examining the UWE based research on the prevention, treatment and community integration of people impacted by sexual abuse. The book discusses policy, practice, theory and research in this area with the authors reviewing, critiquing, synthesising as well as building upon previous/current research, theory and policy. Kieran McCartan is Professor of Criminology & Health at the University of the West of England, Bristol. Anne Eason is Associate Director of Policing at the University of the West of England, Bristol. Sarah Senker is Director of ATD research & Consultancy and Research Associate in Criminology at the University of the West of England, Bristol. Nick Addis is Senior Lecturer in Criminology at the University of the West of England, Bristol. Cody Porter is Senior Lecturer in Psychology at the University of the West of England, Bristol.